The extent of usage of quantitative techniques in Malaysian business firms - Ku-Mahamud, Ku Ruhana; M. Oktovia, Brigida (Universiti Utara Malaysia, 1996)
A study was conducted to examine the extent of usage of quantitative techniques and the adequancy of computers as support tools in Malaysia business firms. Results indicate that 98% of the respondents used one or more quantitative techniques. These techniques are used in a broad array of functional areas. Lack of knowledge and familiarity among top management personnel were the most common reasons for low use. Findings of this study are related to comparable surveys in the United States and Hong Kong.